Relation between ï¢-carotene and ferritin upon malondialdehyde in Javanese male smoker - Sunarti, Naomi Yoshuantari Ahmad Hamim Sadewa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Smoking of cigarette can cause additional free radicals. Oxidative damage is resulted from the accumulation of freeradicals in the body. Malondialdehyde (MDA) is the end product of free radicals, a marker of oxidative damage. ï¢-carotene is pro-vitamin A, an antioxidant known to quench singlet oxygen. Ferritin is thought to release excessiveiron in smokers, thereby increasing the oxidative stress. The aim of the study is to evaluate the relation between ï¢-carotene and ferritin toward MDA level in Javanese smokers. This study was carried out in a case-control, crosssectional design nested with cluster sampling. Participants were Javanese smokers and non-smokers in Purworejodistrict, Central Java. Samples and data were obtained secondarily. The results were analyzed using independentsamples t-test and linear regression. The results showed that there was very weak negative correlation between ï¢-carotene with MDA (R square=0.013; p value=0.320) and very weak positive correlation between ferritin withMDA (R square=0.043; p value=0.067). There was no statistically significant relation of ï¢-carotene with MDA.Ferritin level was marginally influential upon MDA level as the marker of lipid peroxidation between smokers andnon-smokers. Aging apparently became the confounding variable by influencing the lipid peroxidation more efficientlythan smoking itself (p = 0.013). In conclusion, there was no significant relation between ï¢-carotene and ferritinwith MDA in smokers.Key words : smoking â cigarette â Î²-carotene â ferritin â malondialdehyde